Optical Properties of Nano-Crystalline Cerium Dioxide Synthesized by Single Step Aqueous Citrate-Nitrate Gel Combustion Method - Manoharan, Divinah; Vishista, K. (Asian Journal of Chemistry, 2013)
The present study explores the versatility of aqueous combustion method for preparing powders of varying characteristics suitable for optical application. Combustion synthesis was carried with fuel lean composition which yields crystalline ceria nanoparticles instantaneously. Phase purity of the nanocrystals was confirmed by X-ray diffraction and the average crystallite size was determined to be 5 nm. The surface morphology was analyzed by scanning electron microscopy. The spherical particle size obtained from the transmission electron microscopy was in the range of 4-5 nm. The selected area electron diffraction pattern was completely indexed with the cubic fluorite structure of CeO2. Purity of the sample was confirmed by energy-dispersive X-ray spectroscopy and Fourier-transform infrared spectroscopic analysis. The energy band gap of 3.4 eV was determined from the ultra-violet diffuse reflectance spectra using Kubelka-Munk function and UV-Visible absorption spectra using Tauc plot. The nanoparticles exhibited strong UV absorption and room temperature photoluminescence.